Mechanisms of performance improvements due to a leading teammate during uphill cycling - Ouvrard, T.; Groslambert, A.; Ravier, G.; Grosprêtre, S.; Gimenez, P.; Grappe, F. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To identify the impact of a leading teammate in front of a cyclist on psychological, physiological, biomechanical, and performance parameters during an uphill maximal effort. Methods: After familiarization, 12 well-trained competitive cyclists completed 2 uphill time trials (UTTs, 2.7 km at 7.4%) in randomized order; that is, 1 performed alone (control condition) and 1 followed a simulated teammate during the entire UTT (leader condition). Performance (UTT time) and mean power output (PO) were recorded for each UTT. For physiological parameters, mean heart rate and postexercise blood lactate concentration were recorded. Psychological parameters (rating of perceived exertion, pleasure, and attentional focus) were collected at the end of each trial. Results: Performance (UTT time) significantly improved by 4.2% (3.1%) in the leader condition, mainly due to drafting decrease of the aerodynamic drag (58% of total performance gains) and higher end spurt (+9.1% [9.1%] of mean PO in the last 10% of the UTT). However, heart rate and postexercise blood lactate concentration were not significantly different between conditions. From a psychological aspect, higher pleasure was observed in the leader condition (+41.1% [51.7%]), but attentional focus was not significantly different. Conclusions: The presence of a leading teammate during uphill cycling had a strong impact on performance, enabling higher speed for the same mean PO and greater end spurt. These results explain why the best teams competing for the general classification of the most prestigious and contested races like the Grand Tours tend to always protect their leader with teammates during decisive ascents.